The Effect of Talking Chips Technique Toward the Improvement of Students’ Speaking Achievement at one of the Senior High Schools in Bandung - Syafryadin Syafryadin (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2020)
This study investigated how the Talking Chips Technique can help students to improve their speaking. The sample was only one class and total number of students was 36 students. This study used a time series design and three data collection, i.e. note taking, participant observation, and speaking test. The data from observation were analyzed by using thematic analysis and band score of speaking. This study was conducted by using multiple pre-test and post-test. Therefore, the findings of this study were based on pre- test, treatments and post- test. During the treatments, there were problems related to classroom management (noisy, low participation, laughing), fluency (pause, flow and speed) and accuracy (pronunciation, grammar and vocabulary). Those problems could be minimized. After post-test, there were still problems, but the problems were fewer than previous ones like only fluency and accuracy because students had showed the awareness and enthusiasm in speaking English. This study showed the improvement of students’ speaking achievement from treatment until posttest. It was proved by the mean score pretest and posttest. In pre-test, the mean score of fluency was 61.1 and 62.81 for accuracy. In post-test, the mean score of fluency was 71.451 and accuracy was 74.69. Then, t- test for fluency was 7.05 and t-test for accuracy was 8.31 with t critical or table was 2.031. It meant that H1 was accepted. There was significance improvement of students’ speaking in terms of fluency and accuracy. The findings suggest that the students still need further treatments to improve their speaking even though they have achieved the target.